The Role of Nutritional Supplementation in Hypothyroidism: A Review - Chodkowski, Jakub (Quality in Sport, 2024)
Introduction: Hypothyroidism is a common endocrine disorder, which affects metabolism and quality of life and often requires lifelong management. Recent studies suggest that nutritional factors, such as iodine, selenium, zinc, and vitamin D, may play a role in thyroid function and symptom management. This systematic review aims to evaluate the effects of specific nutrients and dietary patterns on hypothyroid outcomes, synthesizing evidence to provide dietary guidance for individuals with hypothyroidism and autoimmune thyroid disorders. Materials and Methods: Comprehensive literature review was conducted across databases, including PubMed and Google Scholar for studies published between 2000 and 2023. Inclusion criteria targeted peer-reviewed clinical trials, cohort studies, and meta-analyses examining the impact of nutritional interventions on thyroid function and symptom improvement in hypothyroid patients. Results: Findings indicate that iodine and selenium supplementation support thyroid hormone production and immune regulation in hypothyroidism, especially autoimmune types. Vitamin D and zinc appear beneficial for reducing fatigue and enhancing metabolic function. However, nutrient interactions with thyroid medication warrant careful management. Conclusions: Nutritional interventions may enhance hypothyroidism management, but individualized approaches are essential. Further large-scale studies are needed to establish clear guidelines, integrating nutrition as a complementary strategy alongside traditional therapies for optimal patient outcomes.